Accommodating Students’ Varied Learning Styles In The Classroom - Novia Russilawatie; Anang Widodo (Universitas Teknologi Yogyakarta, 2020)
People depend on their senses to process the information around them. Most people tend to use one of their senses more than the others. Each individual has a preferred learning style, and many have multiple learning styles. One particular style is not better than the others and a preferred style does not mean one cannot learn in other ways. Students should know what may work best for them to process, learn and retain information. They may become better learners if they know their learning styles and use the respective strategies. From the study which has been conducted in University of Technology Yogyakarta, the learning styles of students of non-English departments are predicted to be influential to their English Proficiency Test. Therefore, teachers need to be aware of there being varied learning styles in their classes. This study examined primary data in the form of students’ learning styles at the University of Technology Yogyakarta, which were analyzed quantitatively with an ex-post facto design. Respondents were non-English Department UTY students totaling 150 students who participated in the English Proficiency Test during September - December 2019. In addition to primary data, which were collected using a questionnaire technique, this study also analyzed secondary data from other studies related to learning styles, especially VAK learning styles (Visual, Auditory and Kinesthetic). The results showed that students' learning styles had an effect on their English Proficiency Test score acquisition. Secondary data analysis produces recommendations for English teachers on how they can accommodate students' different learning styles in designing classroom learning for better learning outcomes. Keywords: learning style, primary data, secondary data, VAK.